Assessing Nuclear Security Risks in Pakistan - Sitara Noor (International Journal of Nuclear Security, 2023)
Pakistan’s nuclear program and perceived nuclear security concerns have attracted global attention. The varying concerns range from the potential theft of nuclear weapons or materials to the unauthorized use of a nuclear device to terrorist groups taking control of the Pakistani government. The enduring debate, however, has oscillated between these doomsday scenarios and some optimistic considerations, where various quarters have shared their satisfaction over Pakistan’s nuclear security regime and its ability to deal with the emerging challenges. To address the evolving nature of these threats, Pakistan is constantly improving its nuclear security infrastructure. It has established a comprehensive legislative and institutional structure, nuclear security systems, and has also undertaken various international obligations. To further improve nuclear security perceptions, Pakistan should adopt a more transparent approach and learn from international best practices.
Keywords: Nuclear Security; IAEA; Nuclear; Terrorism; Physical Protection